Role of pirfenidone in the management of pulmonary fibrosis - Meyer KC (Therapeutics and Clinical Risk Management, 2017)
Keith C Meyer,1,2 Catherine A Decker3,4 1University of Wisconsin Lung Transplant and Advanced Lung Disease Program, 2Department of Medicine, Section of Allergy, Pulmonary and Critical Care Medicine, Clinical Sciences Center, University of Wisconsin School of Medicine and Public Health, 3Department of Pharmacy, 4Department of Pulmonary Medicine, University of Wisconsin Hospital and Clinics, Madison, WI, USA Abstract: Pulmonary fibrosis is associated with a number of specific forms of interstitial lung disease (ILD) and can lead to progressive decline in lung function, poor quality of life, and, ultimately, early death. Idiopathic pulmonary fibrosis (IPF), the most common fibrotic ILD, affects up to 1 in 200 elderly individuals and has a median survival that ranges from 3 to 5 years following initial diagnosis. IPF has not been shown to respond to immunomodulatory therapies, but recent trials with novel antifibrotic agents have demonstrated lessening of lung function decline over time. Pirfenidone has been shown to significantly slow decline in forced vital capacity (FVC) over time and prolong progression-free survival, which led to its licensing by the United States Food and Drug Administration (FDA) in 2014 for the treatment of patients with IPF. However, pirfenidone has been associated with significant side effects, and patients treated with pirfenidone must be carefully monitored. We review recent and ongoing clinical research and experience with pirfenidone as a pharmacologic therapy for patients with IPF, provide a suggested approach to incorporate pirfenidone into a treatment algorithm for patients with IPF, and examine the potential of pirfenidone as a treatment for non-IPF forms of ILD accompanied by progressive pulmonary fibrosis. Keywords: idiopathic pulmonary fibrosis, treatments, pirfenidone, interstitial lung disease